PENGARUH METODE PENDIDIKAN SEBAYA DAN METODE CERAMAH TERHADAP PENGETAHUAN DAN SIKAP SISWA TENTANG NAPZA DI SMA PAB 4 SAMPALI PERCUT SEI TUAN 2016 - Ermawaty Arisandi (Elisabeth Health Jurnal, 2016)
Today, drug abuse is commonly done such as high school and college students; 65% of them used drugs in 2011. The most effective strategy of preventing from and handling napza in changing adolescents’ behavior is through health education such as peer education and interactive lecture. The objective of the research was to find out the influence of peer education and interactive lecture on students’ knowledge and attitude at SMA PAB 4 Sampali, Percut Sei Tuan. The research used quasi experiment. The population was 160 students and 60 of them were used as the samples with 30 of them were in the peer education and the 30 students in interactive lecture. The data were gathered by using questionnaires and analyzed by using paired t-test, Wilcoxon and Mann-Whitney test. The result of the research showed that health education with interactive lecture had the influence on the increase in students’ knowledge (p<0.001) and attitude (p<0.001) toward napza. Health education with peer education had the influence on the increase in students’ knowledge (p<0.001) and attitude (p<0.001) toward napza. Health education with peer education was more effective in knowledge and attitude than interactive lecture. It is recommended that the school management make the policy on any activity in increasing information about napza to adolescents by providing peer education since it is the most appropriate for adolescents. It is also recommended that the management of BNN make ex-napza users participate in health education.